1982
DOI: 10.1111/j.1365-2133.1982.tb00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dermatophyte infections. I. Clinical and mycological features

Abstract: One hundred and six patients with chronic dermatophytosis unresponsive to griseofulvin were studied. Trichophyton rubrum was the causative organism in 93% of cases. Chronic dermatophyte infections caused by organisms other than T. rubrum occurred predominantly, but not exclusively, in patients with underlying diseases. Forty-nine percent of the patients had a personal or family history of atopy but other abnormalities included disorders of keratinization, collagen vascular disease and systemic steroid therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 14 publications
5
50
0
2
Order By: Relevance
“…Nucleotide and deduced amino acid sequences of recombinant Tri r 4. The NH 2 -terminal amino acid residues (positions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] contain the conserved features of a signal peptide with a predicted cleavage site between Ala 19 and Phe 20 . Underlined regions represent amino acid sequences previously obtained for the NH 2 terminus and for six enzymatically generated peptides of natural Tri t 4.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleotide and deduced amino acid sequences of recombinant Tri r 4. The NH 2 -terminal amino acid residues (positions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] contain the conserved features of a signal peptide with a predicted cleavage site between Ala 19 and Phe 20 . Underlined regions represent amino acid sequences previously obtained for the NH 2 terminus and for six enzymatically generated peptides of natural Tri t 4.…”
Section: Methodsmentioning
confidence: 99%
“…They further obtained evi dence that type I hypersensitivity in atopic subjects antag onizes the effect of cellular immunity locally [21]. They concluded that deficient or compromised cellular immuni ty is a correlate of susceptibility to dermatophyte infec tions from a study of experimental dermatophytosis in naturally infected subjects [22], In vitro assays of T lym phocyte functions also demonstrated a deficiency of cellu lar immunity as well as a high incidence of atopy in indi viduals with chronic dermatophytosis [23][24][25], Another interesting point about the chronicity is the high incidence of palmoplantar infections [25] and that of T.rubrum infections [26]. both of which are associated with low in vitro T lymphocyte reactivity.…”
Section: Chronic Dermatophyte Infectionsmentioning
confidence: 95%
“…As early as 1949, a high incidence of allergic history in patients with chronic dermatophytosis was reported (48,61,63). Although elevated total IgE levels in the serum of patients with chronic dermatophytosis have been reported (7), normal IgE levels have also been observed among individuals with athlete's foot, irrespective of atopic history (87).…”
Section: Background: Historical Perspectivementioning
confidence: 99%